2010
DOI: 10.3390/molecules15031127
|View full text |Cite
|
Sign up to set email alerts
|

Selection and Characterization of DNA Aptamers for Egg White Lysozyme

Abstract: We have selected aptamers binding to lysozyme from a DNA library using capillary electrophoresis-systematic evolution of ligands by exponential enrichment. During the selection process the dissociation constant of the ssDNA pool decreased from the micromolar to the low nanomolar range within five rounds of selection. The final aptamer had a dissociation constant of 2.8 ± 0.3 nM, 6.1 ± 0.5 nM, and 52.9 ± 9.1 nM as determined by fluorescence anisotropy, surface plasmon resonance and affinity capillary electropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 37 publications
2
69
0
Order By: Relevance
“…-- (Tran et al, 2010) DNA 3 nM Electrochemical (voltammetry) 0.5 µg/mL (Cheng et al, 2007) (Kirby et al, 2004) RNAFluorescence (microarray) 70 fM (Collett et al, 2005) Section 2.3 will describe these systems briefly, while three biosensor platforms targeting pathogens in food will be discussed in Section 2.4.…”
Section: Aptamers For Pathogenic Food Safety Targetsmentioning
confidence: 99%
“…-- (Tran et al, 2010) DNA 3 nM Electrochemical (voltammetry) 0.5 µg/mL (Cheng et al, 2007) (Kirby et al, 2004) RNAFluorescence (microarray) 70 fM (Collett et al, 2005) Section 2.3 will describe these systems briefly, while three biosensor platforms targeting pathogens in food will be discussed in Section 2.4.…”
Section: Aptamers For Pathogenic Food Safety Targetsmentioning
confidence: 99%
“…By using electrochemical impedance spectroscopy (EIS) on screen-printed carbon electrodes [63], it was demonstrated that the lowest detection limit and wider linear range can be achieved using the aptamer proposed by Tran et al [71]. More recent studies showed that using a mixture of two aptamer sequences with different affinities allows an improved control of the sensitivity and linear range of aptasensors [72].…”
Section: Aptamer-based Electrochemical Lysozyme Sensorsmentioning
confidence: 99%
“…Based on these results, Kirby et al [70] have developed a reusable bead-based electronic tongue sensor arrays of anti-lysozyme aptamers for the detection of proteins, where fluorescence labeling is involved. Using capillary electrophoresis-SELEX, a new lysozyme aptamer characterized by an order of magnitude increased affinity was selected (Table 1) [71]. Based on these new bioreceptors, electrochemical sensors emerged as alternative devices able to offer alternative lysozyme sensing strategies.…”
Section: Quantification Methodsmentioning
confidence: 99%
See 2 more Smart Citations